Endocrine disrupting chemicals and the growth of environmental health in Israel - Falk Henry (BMC, 2012)
Abstract This commentary addresses the article by Berman, et al. on reproductive health trends in Israel potentially related to endocrine disrupting chemicals (EDCs) and on associated health policy decisions in Israel to prevent long-term effects from exposure to EDCs. There are intensive, ongoing research efforts in the US that will provide additional guidance on this issue in the future. The commentary also notes and commends the growing capacity and resources for environmental health work in government and academia in Israel.